The Map Trap - Clements, Andrew 1949- (New York : Atheneum Books for Young Readers, 2014)
Sixth-grader Alton Barnes loves maps, and when his portfolio of secret maps is stolen, he begins getting notes with orders that he must obey to get the maps back but, with the help of a popular classmate, he just might succeed before his teacher, principal, or someone else learns he has been studying and mapping things about them.
Keywords: Maps -- Fiction; Cartography -- Fiction; Schools -- Fiction; Friendship -- Fiction; Stealing -- Fiction; Mystery and detective stories; Maps -- Juvenile fiction; Cartography -- Juvenile fiction; Schools -- Juvenile fiction; Friendship -- Juvenile fiction; Stealing -- Juvenile fiction; JUVENILE FICTION / School & Education; JUVENILE FICTION / Family / General (see also headings under Social Issues); JUVENILE FICTION / Social Issues / Friendship; Detective and mystery stories